ANALISIS KINERJA EVAPORATOR PADA SISTEM ORGANIC RANKINE CYCLE KAPASITAS 500KW - Wahidin, Wahidin; Gaos, Yogi Sirodz; Wiradinata, Irvan (ALMIKANIKA, 2019)
This research is observes an evaporator performance in the Organic Rankine Cycle (ORC) 500 kW power plant. The purpose of this research is to analyse the efficiency and performance the evaporator. The working fluid used in this ORC system is n-pentane (C5H12). Several parameters which were taken into consideration during the thermal calculation are: Thermodynamic; Properties of working fluid based on Refrop; and the ORC’s efficiency. Moreover, this research used Heat Transfer Research Inc (HTRI) in order to compare manual and software-based calculation. This calculation shows that 8,64 percent overdesign deviation (1741 tube by manual calculation while 1782 by software-base calculation). Data obtained for this research shows that the hot water circulation in the tube side has a mass flow of 28.828 kg/s, an inlet temperature of 164.99 C , an outlet temperature of 134.99 C . Meanwhile, in the shell side (n-pentane) has an inlet temperature of 91.61 C , an outlet temperature of 140.43 C and a mass flow 10.213 kg/s. The results show that the evaporator has an efficiency of 66.5 percent, Q hot water ( = 3632 kW, latent heat and sensible heat = 3886.95 kW.